Cosmus Aqua : mágico zoom de retratos invisibles (2017)
The microscopic world is an incredibly enigmatic world; Enriched with a number of microorganisms, cycles of life, underworlds difficult to perceive before our eyes because of their tiny size. This micro world, forms of life that we can not contemplate with the naked eye, are now available to all of us, human beings; This is a portion of that small reality that our limited capacity of vision does not let us capture. This aquatic richness is present in different corners of our planet, organisms destined to fulfill determined functions in the existing ecosystems. Colombia, has a magical little world that has been explored in different ways; A cosmos that has not been known by all, but by some. It is for this reason that I conduct my research on the importance of one of the spaces or natural reserves present in our country, specifically in Bogota; The wetlands. While understanding that there is a hidden richness in these bodies of water, which has not been perceived before our eyes, relate our interest and awareness with knowledge, taking into account that we do not care for what we do not know, that which is not Tangible or visible does not generate greater impact to our reality. Making visible the invisible is my slogan to create awareness of the importance of water in the Kennedy community, showing the potential of the imperceptible or inadvertent, specifically the microscopic world; Generating new knowledge about the interest of the tiny life behind the contamination of a wetland, developing a traveling system or classroom, Cosmus Aqua, traveling classroom that brings us to a magical zoom that leads us to hidden or inadvertent territories, a space of immersion Permitting us to connect with those unexplored beings existing in a single drop of water.--Tomado del Formato de Documento de Grado.